2018
DOI: 10.1128/msphere.00583-17
|View full text |Cite
|
Sign up to set email alerts
|

Assembly, Biochemical Characterization, Immunogenicity, Adjuvanticity, and Efficacy of Shigella Artificial Invaplex

Abstract: The native Invaplex (Invaplex) vaccine and adjuvant is an ion exchange-purified product derived from the water extract of virulent species. The key component of Invaplex is a high-molecular-mass complex (HMMC) consisting of the lipopolysaccharide (LPS) and the invasin proteins IpaB and IpaC. To improve product purity and immunogenicity, artificial Invaplex (Invaplex) was developed using recombinant IpaB and IpaC proteins and purified LPS to assemble an HMMC consisting of all three components. Characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 51 publications
0
60
0
1
Order By: Relevance
“…The top-10 antigen list (representative of the greatest mean antibody responses) was populated with proteins that constitute the Shigella T3SS, a needlelike structure that promotes invasion of the host cell by delivering effector proteins from the bacterium into the host cytoplasm ( 40 , 41 ). Of these, the microarray confirmed immunoreactivity to IpaB, -C, and -D, which have been included in several vaccine candidate approaches, including Invaplex (LPS plus IpaB, IpaC, and IpaD) ( 42 ); IpaB and IpaD delivered mucosally ( 43 ); IpaB and IpaD delivered parenterally with adjuvants ( 44 46 ); an IpaBD fusion ( 45 ); and IpaB, -C, and -D-containing outer membrane vesicles ( 47 ). Invaplex was shown to be immunogenic in humans ( 33 ), and the remaining candidates were shown to be protective in animals (reviewed in reference 8 ).…”
Section: Discussionmentioning
confidence: 88%
“…The top-10 antigen list (representative of the greatest mean antibody responses) was populated with proteins that constitute the Shigella T3SS, a needlelike structure that promotes invasion of the host cell by delivering effector proteins from the bacterium into the host cytoplasm ( 40 , 41 ). Of these, the microarray confirmed immunoreactivity to IpaB, -C, and -D, which have been included in several vaccine candidate approaches, including Invaplex (LPS plus IpaB, IpaC, and IpaD) ( 42 ); IpaB and IpaD delivered mucosally ( 43 ); IpaB and IpaD delivered parenterally with adjuvants ( 44 46 ); an IpaBD fusion ( 45 ); and IpaB, -C, and -D-containing outer membrane vesicles ( 47 ). Invaplex was shown to be immunogenic in humans ( 33 ), and the remaining candidates were shown to be protective in animals (reviewed in reference 8 ).…”
Section: Discussionmentioning
confidence: 88%
“…At present, studies in humans and animals have shown that protection by vaccination is possible. Potential candidates for Shigella vaccines include glycoconjugate vaccines, such as recombinant glycoconjugate, synthetic glycoconjugate, O -polysaccharide covalently linked to immunogenic carrier proteins,177,178 virG-based live attenuated (WRSS1, WRSs3, WRSf3, WRSf2G12, WRSf2G15and WRSd1),179,180 recombinant outer-membrane proteins,181 live attenuated vaccines,182,183 invasion-plasmid antigens B, C, and D,184 DNA-based vaccines, Ty21a typhoid vaccine expressing Shigella LPS,185 recombinant probiotic–based candidates,186 and whole-cell-killed and Shigella trivalent inactivated whole-cell and heat-killed multiserotype Shigella ,187,188 as well as novel antigen candidates, such as triacylated S-LPS, subcellular complexes purified from virulent cultures (Invaplex),189 GMMA protein particles,190 and an OMV-NP vaccine (Table 3). 191…”
Section: Novel Therapeutic Strategies For Shigella Treatmentmentioning
confidence: 99%
“…In contrast to purified high molecular weight capsular polysaccharides, which are well-established licensed vaccines for use in human, endotoxicity precludes the use of LPS as a parenterally administered immunogen. Instead, formulations whereby LPS toxicity is masked as in Invaplex, 29 reduced and even abolished as in GMMA 30 or encompassing LPS derivatives devoid of toxicity, especially in the form of protein conjugates, were investigated.…”
Section: Lipopolysaccharide-based Vaccine Candidatesmentioning
confidence: 99%